Pergantian Auditor, Independensi Auditor, Dan Kompetensi Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik Wilayah Kota Bandung - Effendi, Yusup; Kusumawardani, Astrin; Herlina, Listri (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to analyze the effect of auditor rotation, auditor independence, and auditor competence on audit quality at public accounting firms in the Bandung City area. The study used quantitative methods with data collection techniques through questionnaires. The research sample consisted of 37 auditors who worked at public accounting firms in Bandung City. The data were analyzed using multiple linear regression analysis with the help of SPSS. The results showed that: (1) Auditor rotation has a significant effect on Audit Quality with a significance value of 0.022 <0.05; (2) Auditor independence has a significant effect on Audit Quality with a significance value of 0.000 <0.05; and (3) Auditor competence has a significant effect on Audit Quality with a significance value of 0.000 <0.05. The R Square value of 0.933 indicates that 93.3% of the variation in Audit Quality can be explained by the three independent variables. This study provides practical implications for public accounting firms in improving audit quality through the implementation of auditor rotation policies, strengthening independence, and developing auditor competence.